2011
DOI: 10.1038/sc.2011.49
|View full text |Cite
|
Sign up to set email alerts
|

Association of spasticity and life satisfaction after spinal cord injury

Abstract: ObjectiveTo identify the relationship between spasticity and life satisfaction as measured by 3 multi-item factor scales and a rating of overall quality of life among participants with spinal cord injury (SCI).Study DesignCross-sectional survey; secondary analysis of existing data by linear regression analysis between spasticity and quality of life.SettingLarge specialty hospital in the Southeastern United States.MethodsParticipants included 1,549 adults with traumatic spinal cord injuries, at least 18 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 19 publications
1
45
0
Order By: Relevance
“…Pressure ulcers was found in 9.9% of the non-traumatic SCI patients and in 17.6% of the traumatic SCI patients. Another study reported this ratio to be 31.3% in the non-traumatic SCI patients and in the traumatic SCI group, it has been reported to be 41.8% and 23.7% (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Pressure ulcers was found in 9.9% of the non-traumatic SCI patients and in 17.6% of the traumatic SCI patients. Another study reported this ratio to be 31.3% in the non-traumatic SCI patients and in the traumatic SCI group, it has been reported to be 41.8% and 23.7% (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…1 These common disabling conditions negatively affect mood, sleep, quality of life, and participation in activities and active recreation as well as employment. [2][3][4][5][6][7] Neuropathic pain is present in 50-60% and spasticity in about 70% of individuals living with a SCI. 5,[8][9][10][11] Neuropathic pain is a multidimensional constellation of phenomenologically different symptoms and is defined as 'pain caused by a lesion or disease of the somatosensory nervous system'.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 1549 adults with SCI, Westerkam et al. evaluated multiple measures of life satisfaction and demonstrated that spasticity is negatively correlated with quality of life after SCI . Henze et al.…”
Section: Patient Populations Most Affected By Spasticity and Dystoniamentioning
confidence: 99%